Hate Speech Analysis on Social Media: A Case Study of Instagram and TikTok Comment Sections Targeting the Governor of Aceh (2025-2030) - Eviyana; Muhammad Iqbal; Juni Ahyar (Global Action and Education for Society, 2026)
This study aims to analyze the forms of hate speech found in the comment sections of Instagram and TikTok accounts discussing the Governor of Aceh for the 2025–2030 term. The background of this research stems from the growing phenomenon of hate speech on social media, which often targets public figures particularly regional officials potentially influencing public image and trust. This research employs a descriptive qualitative method, with data collection techniques including reading, documentation, and note-taking on comments containing hate speech. The data were analyzed based on hate speech categories according to the Indonesian National Police Circular, R. Soesilo (in Permatasari & Subyantoro), the Indonesian Dictionary (KBBI), and other relevant theories on hate speech. The results indicate that there are 62 comments containing hate speech, consisting of 45 insults, 11 cases of defamation, 1 blasphemy, 3 instances of provocation, and 2 hoaxes. The most dominant category is insults, followed by defamation. This study concludes that social media has become a vulnerable space for the dissemination of hate speech, particularly in the context of local political issues. These findings are expected to provide input for the public to engage more wisely in online discourse and for authorities to strengthen digital literacy and law enforcement.